Historical demography of Coereba flaveola on Puerto Rico. (6th April 2019) - Humphries, Meghann B; Barbosa De Oliveira Pil, Maria W; Latta, Steven C; Marra, Peter P; Ricklefs, Robert E
Abstract: We use contemporary genetic diversity to characterize the within-island population structure and historical demography of Bananaquits (Aves: Thraupidae: Coerebinae: Coereba flaveola ) on the West Indian island of Puerto Rico (Greater Antilles). We relate periods of population expansion, from Puerto Rico across the Lesser Antilles, to the genetic architecture of the source population, and describe differentiation of populations within Puerto Rico. Lastly, we report comparable analyses of populations of Bananaquits on Jamaica and of a related species, the Black-faced Grassquit (Coerebinae: Tiaris bicolor ), on Puerto Rico. We found differentiation among contemporary populations of Bananaquits within Puerto Rico and signatures of renewed demographic expansion in eastern Puerto Rico beginning 100 kyr ago and, in the western portion of the island, 40 kyr ago. Populations of T. bicolor on Puerto Rico exhibit similar structure to Bananaquits, while Bananaquits on Jamaica exhibit no differentiation among locations. Both T. bicolor and Jamaican C. flaveola provide mixed evidence of demographic expansion.